A COST-BENEFIT PERSPECTIVE ON THE WORK-FROM-HOME SETUP: LIVED EXPERIENCES OF PRIVATE SCHOOL TEACHERS IN THE PHILIPPINE CONTEXT - Lopez, Maria Cristy Felipa L. (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study explored the lived experiences of teachers from selected schools in Cauayan, Isabela, who transitioned to a work-from-home (WFH) arrangement during the COVID-19 pandemic. Guided by Rational Choice Theory, the study examined how teachers balanced the challenges and benefits of remote teaching in financial, emotional, and professional terms. A descriptive phenomenological approach rooted in Husserlian philosophy was used. Ten teachers were purposefully chosen, and their experiences were captured through detailed, semi-structured interviews. After transcription, teachers’ statements were grouped into clusters of meaning, which were then examined to identify themes. Six key themes emerged. Some teachers experienced short-term relief from reduced daily expenses, but these savings were quickly consumed by higher costs for utilities and technology. Teachers took part in self-directed learning, which helped their personal and professional growth, while support from their institutions made it easier for them to adjust to remote teaching. Working from home brought certain advantages, like saving on transportation costs and gaining opportunities to develop new skills. At the same time, remote teaching brought challenges, such as higher household expenses, heavier workloads, and a sense of disconnection. The study indicates that teachers showed strong resilience, providing insights that can shape policies to build on current support for their well-being, maintain effective school functioning, and ready the education system for future challenges.